DEVELOPMENT PROCESS OF INCLUSIVE SCHOOLS AND KINDERGARTENS IN MONGOLIA - Разухан, Нурбек; ЖИEНБAEВA , НАДЕЖДА (Pedagogy and Psychology, 2024)
In the article, the authors consider the issues of ensuring that schools and kindergartens are ready in the context of inclusive education, that is, to study the process and difficulties of developing inclusive schools and kindergartens. The research was conducted using document research methods, questionnaire research methods, focus group interview methods, and the Inclusiveness Index, which guides them through the process of developing inclusive schools and kindergartens. An analysis of a number of official documents on inclusive education of children with disabilities in general education schools and the procedure for inclusion of children with disabilities in preschool education services, approved by the orders of the Parliament of Mongolia, the Government of Mongolia, the Minister of Labor and Social Protection of the People, the Minister of Education and Science, the Minister of Health. In the study, school No. 12, kindergarten No. 7 of Darkhan-Uul region, school No. 1, kindergarten No. 8 of Dornod region, comprehensive school "Goviin ireedui" of Dundgovi region, kindergarten No. 3, school No. 105 of Songinokhairkhan district of Ulaanbaatar, kindergarten No. 253 "Support group" members are included. The results presented in the article reveal the problems of further accelerating the development process of inclusive schools and kindergartens in Mongolia, eliminating the identified difficulties, effectively providing quality education services for children, and increasing the comprehensive responsibility of the education sector in order to increase the inclusive competence of teachers.